2000
DOI: 10.1007/s004020050041
|View full text |Cite
|
Sign up to set email alerts
|

The saddle prosthesis in pelvic primary and secondary musculoskeletal tumors: functional results at several postoperative intervals

Abstract: The first purpose of this study was to evaluate the saddle prosthesis in patients with periacetabular tumors in terms of the functional results obtained after several postoperative intervals. The second purpose was to evaluate the complications and how they might be prevented in the future. Functional results according to the MSTS functional rating system were evaluated at several postoperative intervals in 15 patients treated with internal hemipelvectomy and reconstruction with the saddle prosthesis because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 0 publications
3
78
0
1
Order By: Relevance
“…The major complication rate in the present and other series is summarized (Table 3). Among the postoperative complications, deep infection was the most serious and frequent complication also in the present series (32%), similar to other reconstructive procedures; the rates of deep infection have been reported as 18% to 33% in saddle prostheses [4,21,25,28], 25% to 30% in custom-made * Thirteen patients were excluded from MSTS/ISOLS functional evaluation because they died of disease at 4-34 months postoperatively, and another one patient was excluded as a result of hindquarter amputation performed for local recurrence of iliac chondrosarcoma after C-THA; MSTS/ISOLS = Musculoskeletal Tumor Society/International Society of Limb Salvage; F = female; M = male; P-F = proximal femur; MFH = malignant fibrous histiocytoma; GCT = giant cell tumor. * Case series with a mean followup period over 60 months are only listed in Table 2; 15 of 17 patients were primarily treated with an allograft-THA prosthesis composite; à primary malignant bone and soft tissue tumors in 82 patients, solitary metastatic bone tumors in seven, plasmacytoma/myeloma in six, and benign bone tumors in three (fibrous dysplasia two, chondroblastoma one); § the cumulative implant survival rate of C-THA was 67% at 5 and 10 years postoperatively, when patients' death was interpreted as censored to calculate cumulative survival rate.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The major complication rate in the present and other series is summarized (Table 3). Among the postoperative complications, deep infection was the most serious and frequent complication also in the present series (32%), similar to other reconstructive procedures; the rates of deep infection have been reported as 18% to 33% in saddle prostheses [4,21,25,28], 25% to 30% in custom-made * Thirteen patients were excluded from MSTS/ISOLS functional evaluation because they died of disease at 4-34 months postoperatively, and another one patient was excluded as a result of hindquarter amputation performed for local recurrence of iliac chondrosarcoma after C-THA; MSTS/ISOLS = Musculoskeletal Tumor Society/International Society of Limb Salvage; F = female; M = male; P-F = proximal femur; MFH = malignant fibrous histiocytoma; GCT = giant cell tumor. * Case series with a mean followup period over 60 months are only listed in Table 2; 15 of 17 patients were primarily treated with an allograft-THA prosthesis composite; à primary malignant bone and soft tissue tumors in 82 patients, solitary metastatic bone tumors in seven, plasmacytoma/myeloma in six, and benign bone tumors in three (fibrous dysplasia two, chondroblastoma one); § the cumulative implant survival rate of C-THA was 67% at 5 and 10 years postoperatively, when patients' death was interpreted as censored to calculate cumulative survival rate.…”
Section: Discussionsupporting
confidence: 84%
“…However, limb-salvage reconstruction of malignant pelvic tumors, especially in the periacetabular region, remains challenging because of the complex anatomy, the difficulty achieving wide surgical margins, and large bone and soft tissue defects after tumor resection. The reconstructive options include resection arthroplasty [7,30,33], iliofemoral or ischiofemoral arthrodesis [9,12], hip transposition method (pseudarthrosis) [3,12,32], free-vascularized fibular graft for pelvic ring reconstruction [29], allograft [2,22,23,26,39], recycled autologous bone graft [16,20], and endoprosthetic replacement [1,4,11,14,18,21,24,25,27,28,34,[36][37][38]. However, no standard reconstructive procedure exists after internal hemipelvectomy for malignant periacetabular tumors.…”
Section: Introductionmentioning
confidence: 99%
“…There were only a few suitable tumor cases of partial acetabulum involvement. Therefore, ours is like most of the previous reports that consisted of only a few patients [11,22,24]. Moreover, whether partial loss of the acetabulum in the long run will contribute to microscopic instability or accelerated osteoarthritis is still unknown to us.…”
Section: Discussionsupporting
confidence: 53%
“…Although we performed surgery in patients with many co-morbidities (four patients classified as ASA 4) with extended, generalised metastatic disease we had no intra-or postoperative deaths and observed no major complications such as excessive haemorrhage, deep infections, lesions of the femoral nerve, loss of fixation, or dislocations as described in other series after performing various methods for pelvic reconstruction [9,14,15,[17][18][19]. Tillman et al have reported similar results in their series of 19 patients treated with a three-pin modified Harrington technique with respect to occurrence of major intra-and postoperative complications as well as the functional outcome [6].…”
Section: Discussionmentioning
confidence: 98%
“…Although they have reported good results immediately after surgery or during early follow-up, reconstruction failures or degradation of the functional status have been observed in a considerable portion of the patients, especially following implantation of saddle prostheses. Renard et al noted that osteoporosis and insufficient soft tissue quality have affected the functional results in a series of 15 patients treated with saddle prosthesis for periacetabular tumours [14]. A recent study by Jansen et al reported a high risk of complications and poor long-term function in patients following acetabular reconstruction with saddle prostheses after peri-acetabular tumour surgery [15].…”
Section: Discussionmentioning
confidence: 99%